Pengaruh Penggunaan Media Smart Box-Panca Berbasis Madurologi Terhadap Minat Belajar Siswa pada Materi Sila-Sila Pancasila di Kelas II SDIT ABFA Pamekasan - Jannah, Ummi Aisyatus Salehah Ahlul; Sutrisno, Tri (Prodi PGMI STAI Al-Akbar Surabaya, 2025)
This study aims to examine the effect of the Smart Box-Panca learning media based on Madurology on the learning interest of second-grade students in learning the values of Pancasila. The research employed a quantitative approach using a One Group Pretest-Posttest design and involved second-grade students as respondents. Data were collected through learning interest questionnaires administered before and after the learning process and were supported by observations and documentation conducted during the implementation of the learning activities. The analysis was carried out to identify changes in students’ learning interest as well as the extent of the media’s contribution to such changes. The results indicate that the Smart Box–Panca media significantly increased students’ learning interest, as the media was designed with attractive visuals, interactive features, and activities that actively engaged students in the learning process. The integration of Madurese cultural elements through the Madurology approach also helped students feel closer to the learning material, making the learning experience more meaningful and less monotonous. The findings show that the use of Smart Box–Panca media based on Madurology significantly improved students’ learning interest, as evidenced by an increase in the mean learning interest score from 17.84 in the pretest to 31.29 in the posttest, with a mean difference of 13.44 points and a significance value of 0.000 (p < 0.05). Furthermore, simple linear regression analysis revealed that the use of Smart Box-Panca media based on Madurology contributed 12.9% to the improvement of students’ learning interest. These findings confirm that creative learning media aligned with children’s developmental stages constitute an effective strategy for enhancing learning interest in elementary education. This study is important as it provides measurable empirical evidence of the effectiveness of culture-based learning media and opens opportunities for the development of similar media in other subjects and learning contexts.